An empirical analysis of gender bias in education spending in Paraguay - Thomas Masterson (Levy Economics Institute of Bard College, 2008)
Gender affects household spending in two areas that have been widely studied in the literature. One strand documents that greater female bargaining power within households results in a variety of shifts in household production and consumption. An important source of intrahousehold bargaining power is ownership of assets, especially land. Another strand examines gender bias in spending on children. This paper addresses both strands simultaneously. In it, differences in spending on education are examined empirically, at both the household and the individual level. Results are mixed, though the balance of evidence weighs toward pro-male bias in spending on education at the household level. Results also indicate that the relationship between asset ownership and female bargaining power within the household is contingent on the type of asset.
Keywords: C39; D13; J13; J16; 330; Gender bias; education; assets; intrahousehold allocation; Latin America; Paraguay